2011
DOI: 10.1002/chem.201101828
|View full text |Cite
|
Sign up to set email alerts
|

A 5′‐Cap for DNA Probes Binding RNA Target Strands

Abstract: Detecting short RNA strands with high fidelity at any of the bases of their sequence, including the termini, can be challenging, since fraying, wobbling, and refolding all compete with canonical base pairing. We performed a search for 5'-substituents of oligodeoxynucleotides that increase base pairing fidelity at the terminus of duplexes with RNA target strands. From a total of over 70 caps, differing in stacking moiety and linker, a phosphodiester-linked sequence of the residues of L-prolinol, glycine, and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 94 publications
0
24
0
Order By: Relevance
“…For cleavage and deprotection of the DNA, the CPG was treated with aqueous ammonia (27%, 1 ml) and heated to 60EC for 2 h. The oligonucleotides were purified using C18 cartridges (Sep-Pak Vac 3cc) from Waters (Milford, MA, USA) with triethylammonium acetate buffer (0.1 M, pH 7) and a step gradient of CH 3 CN. Molecular caps U AQ and ogOA, shown in Figures 4 and 5, were introduced following the methods described earlier Egetenmeyer, 2011). The analytical data and MALDI-TOF mass spectra of modified oligonucleotides are provided in the supporting information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For cleavage and deprotection of the DNA, the CPG was treated with aqueous ammonia (27%, 1 ml) and heated to 60EC for 2 h. The oligonucleotides were purified using C18 cartridges (Sep-Pak Vac 3cc) from Waters (Milford, MA, USA) with triethylammonium acetate buffer (0.1 M, pH 7) and a step gradient of CH 3 CN. Molecular caps U AQ and ogOA, shown in Figures 4 and 5, were introduced following the methods described earlier Egetenmeyer, 2011). The analytical data and MALDI-TOF mass spectra of modified oligonucleotides are provided in the supporting information.…”
Section: Methodsmentioning
confidence: 99%
“…This length range also encompasses the number of nucleotides found in microRNAs, whose selective detection in clinical samples is a diagnostic challenge (Wark, 2008). It has been previously reported that full length probes perform poorly in detecting microRNAs differing by just one nucleotide (Egetenmeyer, 2011), prompting the question whether segmenting longer hybridization probes into a series of shorter hybridization probes would lead to a better compromise between affinity and selectivity. Here we report the results from an experimental study into this issue.…”
Section: Introductionmentioning
confidence: 99%
“…We will point out the difficulties and limitations of the different strategies and – if available – will show ways to circumvent them. This review focuses strictly on mRNA cap analogues (and some non-natural modifications); for preparation of other capped biomolecules such as capped siRNAs [ 21 ], peptidyl capped oligonucleotides [ 22 ], NAD-capped RNAs [ 23 24 ], 3'-dephospho-CoA linked RNA [ 25 ] or methylphosphate capping [ 26 27 ] we refer to the indicated articles.…”
Section: Introductionmentioning
confidence: 99%
“…High levelso f adaptation and refinement have been achieved in studies on the in vitro evolution of polymerizing enzymes, [1][2][3] and it has been shown that genetici nformation can be stored in and recovered from alternative genetic polymers based on nucleic acid architectures not found in nature. [4] High-yieldinga nalytically powerful nonenzymatic polymerization methodologies have also been developed, [5][6][7][8][9][10][11][12][13] enabling in vitro studies on molecular evolution and supporting the Darwinian logics pioneered by Spiegelman. [14] Complex chemistries involved in the nonenzymatic polymerization of highenergy monomers to nucleic acids are well described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiencyo ft he polymerization reactioni sd etermined by the extento fp hosphate activation and the properties of the leaving group. High-yieldingt emplate-directed RNA syntheses are commonly performed with 5'-phosphorimidazoliden ucleosides [9][10][11][12][13][14][15][16] or one of the numerous variants thereof, [17,18] because imidazole and its derivatives are good leaving groups. These are all high-energyc ompounds that polymerizee fficiently,b ut the likelihood of their prebiotic availability and accumulationi s inverselyp roportionalt ot heir intrinsic stability and the elaborate nature of the chemistry necessary fort heir synthesis.…”
Section: Introductionmentioning
confidence: 99%